2017
DOI: 10.3390/molecules22111986
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review on the Significance of Olive Phytochemicals in Plant Physiology and Human Health

Abstract: Olive oil displays remarkable organoleptic and nutritional features, which turn it into a foodstuff appreciated by consumers, and a basic component of the Mediterranean diet. Indeed, the noticed benefits of including olive oil in the diet have been assigned to the presence of diverse bioactive compounds with different molecular structures. These compounds confer a wide range of biological properties to this food matrix, including the prevention of distinct human diseases as well as the modulation of their seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 183 publications
(221 reference statements)
1
60
0
2
Order By: Relevance
“…The most important antioxidant activity of the olive tree phenolic compounds is related to the free-scavenging ability because they inhibit the propagation chain during the oxidation process through the donation of radical hydrogen to alkylproxyl radicals and the formation of stable derivatives during this reaction. These compounds also act as metal chelators, preventing the generation of high concentrations of hydroxyl radicals [41]. This capacity may be reduced by the presence of the -COOOH 3 fragment in several secoirioids structures, because it seems to cause a decrease in the antioxidant activity which is related to the inability of this group to act as an H-donor [42].…”
Section: Functional and Physiological Chemistry Of The Main Secoiridomentioning
confidence: 99%
“…The most important antioxidant activity of the olive tree phenolic compounds is related to the free-scavenging ability because they inhibit the propagation chain during the oxidation process through the donation of radical hydrogen to alkylproxyl radicals and the formation of stable derivatives during this reaction. These compounds also act as metal chelators, preventing the generation of high concentrations of hydroxyl radicals [41]. This capacity may be reduced by the presence of the -COOOH 3 fragment in several secoirioids structures, because it seems to cause a decrease in the antioxidant activity which is related to the inability of this group to act as an H-donor [42].…”
Section: Functional and Physiological Chemistry Of The Main Secoiridomentioning
confidence: 99%
“…In particular, 3-hydroxytyrosol, an olive oil polyphenol, plays a remarkable role against reactive oxygen species (ROS) that cause cellular damage. Studies in animals and humans have shown that polyphenol components of OMW exhibit important biological activities that can prevent oxidative stressassociated diseases (13,27). Recent studies of our research group showed broiler chickens and piglets given feed supplemented with OMW exhibited an increased antioxidant capacity in blood and tissues (10,28).…”
mentioning
confidence: 93%
“…In recent years, there is evidence that bioactive compounds present in foods possess properties which give them the ability to protect against chronic diseases (11)(12)(13). Studies have shown that in farm animals, oxidative stress is involved in various pathological situations, directly related to animal welfare (14).…”
mentioning
confidence: 99%
“…Overall, the health-promoting effects of EVOO are mainly related to its inherent chemical composition, such as the fatty acid profile [6] rather than other "minor" components (nearly 2% of the total weight). This quantitatively lower fraction includes more than 200 chemically different compounds belonging to aliphatic alcohols, terpenoids, sterols, pigments, volatile compounds and (poly)-phenolic compounds [7,8]. EVOO is reported to contain at least 30 phenolic compounds, including phenolic acids and derivatives, phenolic alcohols, secoiridoids, lignans and flavones [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible explanations is that limited information is reported in the literature regarding the modifications of EVOO phytochemicals during the gastrointestinal processes. Overall, the highest plasma concentration of polyphenols and derived metabolites is recorded from 1 to 3 h after ingestion, thus clearly indicating that their major absorption takes place in the small intestine [7]. To date, few studies regarding the impact of a simulated gastrointestinal digestion method on the comprehensive modification of EVOO bioactive compounds have been reported.…”
Section: Introductionmentioning
confidence: 99%